Tangency and multiple factors of violence against lecturer: nuances of the experience in pedagogical practices in health education - Angela Gilda Alves; Flaviane Cristina Rocha César; Maria Alves Barbosa; Lizete Malagoni de Almeida Cavalcante Oliveira; Dolors Rodríguez-Martín; Edinamar Aparecida Santos da Silva; Johnatan Martins Sousa; Sara Oliveira Souza (Revista Brasileira de Enfermagem, 2022)
ABSTRACT Objective: to identify factors that lead the teacher to experience violence in their pedagogical practice in health education. Method: research with a qualitative approach, based on the Grounded Theory, conducted with 11 professors of the nursing course of a public university in the central region of Brazil in 2020 and 2021. Online semi-structured interviews were analyzed partially in the light of the Constructivist Grounded Theory. Results: factors that lead lecturer to experience violence are characterized by institutional culture, gender, professor’s perception of violence, and the triggers that drive students to commit violence. Social status and inequalities lead to positions of domination and, consequently, create a fertile ground for violence. Final Considerations: analyzing violence under Bourdieu’s theory, it is clear that student violence towards lecturer and the reports contained in this study deserve pedagogical reflection. However, it is necessary to include these discussions as a background in teaching environments.